ChemInform Abstract: Catalyst Free Synthesis of Fused Pyrido[2, 3‐d]pyrimidines and Pyrazolo[3, 4‐b]pyridines in Water. Issue 10 (7th March 2013) - Rahmati, Abbas; Khalesi, Zahra
Abstract One‐pot three‐component condensations of heterocyclic amines (I) or (V) with benzoyl acetonitrile and aromatic aldehydes give pyridopyrimidines (IV), and pyrazolopyridines (VI), resp., in good yields.